Evaluation of osteogenic properties after application of hydroxyapatite-based shells of Portunus pelagicus - Michael Josef Kridanto Kamadjaja; Alya Nisrina Sajidah Gatia; Agtadilla Novitananda; Lintang Maudina; Harry Laksono; Agus Dahlan; Bambang Agustono Satmoko Tumali; Muhammad Dimas Aditya Ari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: After tooth extraction, the socket leaves a defect on the alveolar bone. The administration of shell crab-derived hydroxyapatite maintains bone dimensions that are important for achieving successful prosthodontic treatment. Purpose: The aim of the study was to determine the osteogenic properties, such as the number of osteoclasts, osteoblasts and osteocytes, after the application of hydroxyapatite-based shell crab in the post-extraction sockets of Wistar rats. Methods: There were two groups: the control group (K) and the treatment group (T). Wistar rats were randomly divided into control and treatment groups. After tooth extraction, hydroxyapatite gel derived from Portunus pelagicus shells was applied to the tooth sockets of Wistar rats. Observations and calculations of osteoclasts, osteoblasts and osteocytes were carried out on the 14th and 28th days under a light microscope with 400 times magnification. Statistical analysis was performed using one-way ANOVA. Results: There was a significant difference (p<0.05) between the K14 and P14 groups, K28 and P28 groups, K14 and K28 groups, and P14 and P28 groups. The results indicated that there were significant differences between groups of variables. Conclusion: The application of shell crab-derived hydroxyapatite (Portunus pelagicus) was able to decrease the number of osteoclasts and increase the number of osteoblasts and osteocytes.